WHAT WAS THE PRINCE CATHEDRAL IN KRYLOS BUILT OF? - PASTERNAK, Severyn (Halych. Scientific work collection, 2023)
In this brief article, engineer Severyn Pasternak (1899–1994) thoroughly analyzes the building materials of the Assumption Cathedral on the territory of ancient Halych, as discovered by his well-known brother, archaeologist Yaroslav Pasternak (1892–1969). Among the materials mentioned are alabaster, travertine, Turonian chalk, Lithothamnium limestone, and Devonian sandstone. The author also puts forward hypotheses about the locality from which these stones could have been transported. The survey was published in the printed journal of the Ukrainian Regional Tourism Society «Plai» – «Our Homeland». Philological features are preserved in accordance with the original text and the Ukrainian spelling used in Halychyna in 1938.